SINGLE-LAYER BLUE LEDS BASED ON A PEROVSKITE– POLYMER COMPOSITE (Universal International Scientific Journal, 2026)
A practical solution to the challenge of simple and stable blue LEDs is proposed:a solution-processed single-layer device based on a perovskite–polymer composite. Stable blueelectroluminescence at low operating voltages is demonstrated, and prospects for furtheroptimization and practical implementation are outlined.
Keywords: blue LED; halide perovskites; perovskite-polymer composite